Does positive organisational behaviour and career commitment lead to work happiness - Omar, Safiah; Jayasingam, Sharmila; Abu Bakar, Raida (Inderscience, 2019)
This study aims to identify if positive organisational behaviour (POB) and career commitment affect work happiness. Assessment on these two factors were conducted via structural equation modelling. A cross-sectional study comprising 393 ICT professionals working in Malaysia was conducted through a questionnaire survey that was based on the seven-point Likert scale. The research model used was guided by the broaden-and-build theory and the self-determination theory. AMOS version 21 was used for the analyses. Findings indicate that POB has positive relationships with work happiness but career commitment has no significant relationship with work happiness. There was evidence to support that individuals who were positive in nature were more likely to feel happy with their work. There was also evidence to reject the notion that a committed worker was a happy worker. These findings have practical implications on the management and the development of an emerging workforce. Copyright © 2019 Inderscience Enterprises Ltd.